Impact of the Work Environment and Work Motivation in Influencing the Performance of Non-Formal Educators - Djibu, Rusdin; Duludu, Ummyssalam (Journal of Nonformal Education, 2020)
Work Environment and Work Motivation can affect performance in an institution, institution or company. For that, a leader needs to think about it. The purpose of this study was to determine: (1) the influence of the work environment with the performance of Non-formal Educators on the Development Center for Early Childhood Education and Gorontalo Community Education, (2) the effect of work motivation on the performance of Non-Formal Educators at the Center for Early Childhood Education Development and Gorontalo Society Education. (3) the influence of the work environment and work motivation together with the performance of Nonformal Educators for the Development of Early Childhood Education and Gorontalo Community Education. The method used in this research is to use quantitative through remorse techniques to express one variable to another. The population in this study were non-formal educators at the Gorontalo Center for Early Childhood Education and Community Education, which collected 80 people while the sample was a population sample. Data collected through questionnaire distribution. The conclusions of this study are (1) Providing a positive influence on the performance of Non-formal Educators for the Development of Early Childhood Education and Gorontalo Society Education, providing improved environmental performance with the performance of non-formal educators. (2) Providing positive motivation for the performance of Non-formal Educators for the Development of Early Childhood Education and Gorontalo Community Education, providing good motivation for improving the performance of Non-Formal Educators. (3) Making a positive contribution to the work environment and work motivation together to the performance of Non-formal Educators for the Development of Early Childhood Education and Gorontalo Community Education, this means improving the work environment and encouraging work and then improving the performance of Non-formal Educators. The novelty of the research is the performance of Non-formal Educators will be more effective if a leader always provides work motivation regularly and makes a conducive work environment. This research provides knowledge to leaders in improving the performance of Non-formal Educators or teachers, needing to pay attention to motivation and work environment within an institution or company.